The prevalence of multiple sclerosis in Belo Horizonte, Brazil - Marco A. Lana-Peixoto; Elizabeth R. C. Frota; Gilberto B. Campos; Leonardo P. Monteiro (Arquivos de Neuro-Psiquiatria)
Investigations on the prevalence rates of multiple sclerosis (MS) around the world have yielded important clues on the interplay between genetic susceptibility and environmental factors. As Brazil is a huge country laid on many latitudes and inhabited by population with distinct ethnic backgrounds, it might be assumed that the frequency of MS varies in its different regions. Objective: To determine the prevalence rate of MS in Belo Horizonte, the capital of the State of Minas Gerais, Southeastern Brazil. Methods: We used six sources to draw up a provisional list of identified cases of MS. Only patients with diagnosis of clinically definite MS according to Poser Committee criteria were included. Results: The calculated crude MS prevalence was 18.1/100,000 inhabitants. Conclusions: The MS prevalence in Belo Horizonte is similar to that found in São Paulo and Botucatu, two other cities in southeastern Brazil with similar ethnic background.